Fasting Augments PCB Impact on Liver Metabolism in Anadromous Arctic Char - Vijayan, Mathilakath M.; Aluru, Neelakanteswar; Maule, Alec G.; Jørgensen, Even H. (Toxicological Sciences, 2006)
Anadromous arctic char ( Salvelinus alpinus ) undertake short feeding migrations to seawater every summer and accumulate lipids, while the rest of the year is spent in fresh water where the accumulated lipid reserves are mobilized. We tested the hypothesis that winter fasting and the associated polychlorinated biphenyls' (PCBs) redistribution from lipid depots to critical tissues impair the liver metabolic capacity in these animals. Char were administered Aroclor 1254 (0, 1, 10, and 100 mg/kg body mass) orally and maintained for 4 months without feeding to mimic seasonal winter fasting, while fed groups (0 and 100 mg Aroclor 1254/kg) were maintained for comparison. A clear dose-related increase in PCB accumulation and cytochrome P4501A (CYP1A) protein content was observed in the livers of fasted fish. This PCB concentration and CYP1A response with the high dose of Aroclor were 1.5-fold and 3-fold greater in the fasted than in the fed fish, respectively. In fed fish, PCB exposure lowered liver glycogen content, whereas none of the other metabolic indicators were significantly affected. In fasted fish, PCB exposure depressed liver glycogen content and activities of glucose-6-phosphate dehydrogenase, alanine aminotransferase, lactate dehydrogenase, and phosphoenolpyruvate carboxykinase and elevated 3-hydroxyacylcoA dehydrogenase activity and glucocorticoid receptor protein expression. There were no significant impacts of PCB on heat shock protein 70 (hsp70) and hsp90 contents in either fed or fasted fish. Collectively, our study demonstrates that winter emaciation associated with the anadromous lifestyle predisposes arctic char to PCB impact on hepatic metabolism including disruption of the adaptive metabolic responses to extended fasting.